Chronic intermittent hybobaric hypoxia protects against cerebral ischemia via modulation of mitoKATP. (2nd December 2016) - Zhang, Shixiao; Guo, Zan; Yang, Shijie; Ma, Huijuan; Fu, Congrui; Wang, Sheng; Zhang, Yi; Liu, Yixian; Hu, Jie
Highlights: CIHH pretreatment ameliorates learning and memory dysfunction and DND in hippocampus caused by ischemia. CIHH upregulates expression of mitoKATP with or without ischemia. . 5-HD abrogates neuroprotection of CIHH suggesting involvement of mitoKATP . Abstract: Objective: Providing adequate protection against cerebral ischemia remains an unrealized goal. The present study was aimed at testing whether chronic intermittent hypobaric hypoxia (CIHH) would have protective effects against cerebral ischemia and investigating the potential role of mitochondrial membrane ATP-sensitive potassium channel (mitoKATP ) in this effect. Methods: Ischemia was induced in rats by occlusion of bilateral common carotid arteries for 8 min on day 2 after bilateral vertebral arteries were permanently electrocauterized and CIHH was simulated in a hypoxic chamber. Learning and memory impairments were analyzed using the Morris water maze. The delay neuronal death (DND) in the hippocampus CA1 was observed by thionine staining. The expression of the two subunits of mitoKATP, SUR1 and Kir 6.2, and the concentration of cytochrome c (Cyt c) were observed by Western blotting. The mitochondrial membrane potential (Δym) was determined by flow cytometry. Morphological changes of the mitochondria were investigated by electron microscopy. The antagonist of mitoKATP, 5-hydroxydecanoate (5-HD), was used to demonstrate the involvement of mitoKATP . Results: CIHH pretreatment ameliorated the learning and memory impairments produced by ischemia, concomitant with reduced DND in the hippocampus CA1 area. Expression levels of SUR1 and Kir6.2 both increased for at least one week after CIHH pretreatment. Levels of the two subunits were higher in the CIHH pretreatment combined with ischemia group than the ischemia only group at 2 d and 7 d after ischemia. Furthermore, the concentration of Cyt c was decreased in mitochondria and increased in the cytoplasm after ischemia which was prevented by CIHH. The decrease of Δψm and the destruction of mitochondrial ultrastructure were both rescued by CIHH pretreatment. The above protective effects of CIHH were blocked by 5-HD intraperitoneal injection 30 min before ischemia. Conclusion: CIHH pretreatment can reduce cerebral ischemic injury, which is mediated by upregulating the expression and activity of mitoKATP .